Guided waves in aero structure elements - Oh, Boon Kiat (2011)
Structural Health Monitoring is an emerging technology which will one day overshadow non-destructive testing because of its ability to constantly collecting data about the current state of the structures leading to a decrease in ground time of an aircraft. Among the technologies employed, Lamb wave is of particular interest because of its ability to propagate for long distance with relatively high amplitude. This will allow minimal amount of actuators and sensors to be placed on the aircraft. In addition, there is an increasing amount of composites used in aircrafts due to its high strength to weight ratio. However, there is limited knowledge on Lamb wave propagation in composites. Therefore, this report will serve to develop the understanding of the difference in waveform resulting from different defect size in different locations in aero structures made of composites. This was done using PZFlex, a finite element analysis program. In addition, to prove the applicability of these results, actual experiment is carried out to verify the waveform. Through the validation, the results obtained from the modeling can be shown to be accurate. In both computer modeling and experimental set up, the specimen will be excited with low frequency in order to make it easier to analyze the result because only the zero order symmetric mode, S0 and the zero order anti-symmetric mode, A0 will be present. In addition, an investigation into the change in waveform with increasing adhesive thickness was also carried out. However, due to the lack of specimen, this is only done with computer modeling. The results of these computer modeling and experiments can then be used to establish the use of Lamb wave to characterize the defects present in structures.